Empowerment of Youth in Pintu Pohan Village Youth Organization through Entrepreneurship Training in Digital Printing Screen Printing - Marpaung, Nicholas; Siregar, Onan Marakali (Talenta Publisher, 2020)
Fashion as a part of the creative economy today can not only be worked on by people who live in urban areas, but also people who live in villages, especially with the distribution and growth of information technology in the country. People who live in the village do not always have to be farmers or workers in the agrarian sector, but must also have job options that can be a lifestyle to continue to show their existence even though from the village, especially young people who choose to stay in the village. Through this service, we provide screen printing and digital printing training, and provide all the information about the potential and opportunities of this kind of business to the young people in Pintupohan Village, Pintupohan Meranti District, Toba Samosir Regency. By understanding the digital printing technique, it is hoped that it will be able to facilitate printing efforts in larger quantities, and of course provide better economic benefits as well. We also involve speakers and business actors who have been successful in this screen printing business so that participants can face-to-face with business actors and gain more in-depth experience and training. In the future, further dedication is needed which will be focused on a better marketing strategy to continue to support this service activity which is sustainable and effective.